A virtual learning environment to improve antibiotic stewardship in Dentistry - María del Pilar Angarita Díaz; Lilia Jadith Bernal Cepeda; Leidy Bastidas Legarda; Diana Forero Escobar; Angélica Ricaurte Avendaño; Martha Ligia Vergara Mercado; Alejandra Herrera-Herrera; Martha Lucia Rodríguez Paz; Sandra Viviana Cáceres Matta; Natalia Fortich-Mesa; Emilia María Ochoa-Acosta; Youling Lorena Amortegui Vanegas; et al. (Elsevier, 2021)
Aim or Purpose: Optimizing usage of antibiotics is one of the most effective measures that minimize the emergence of antibiotic resistance. This study aimed to develop, implement, and measure the impact of a Virtual Learning Environment (VLE) on Awareness, Attitudes and Intentions to practice (AAIs) regarding antibiotic prescription in Colombian dentists. Materials and Methods: A VLE on antibiotic prescription in dentistry using multimedia resources and an animated character which challenged the participant through different learning moments, was designed. Then, a quasi-experimental multicenter study approved by the ethics subcommittee from the leader University (015-2018), with the participation of 206 dentists from 7 Colombian cities, was performed. To measure the VLE impact, AAIs were compared before and immediately after intervention through a validated questionnaire. Knowledge retention 6 months post-intervention was also assessed. Results: A significantly positive impact on the median of correct answers on AAIs and the level of knowledge (p<0.01, p<0.05) was found. At 6 months, the impact on the median of correct answers on awareness and intentions to practice remained high (p<0.01, p<0.05), however this was not the case for attitudes. Conclusions: The VLE improved awareness and intentions to practice regarding antibiotic stewardship in dentistry; however, more strategies that positively impact attitudes and consciousness on prophylactic use of antibiotics are urgently needed.